3D evaluation of 3DVH program using BANG3 polymer gel dosimeter. Issue 8 (15th July 2013) - Watanabe, Yoichi; Nakaguchi, Yuji
Abstract : Purpose: : With the recent introduction of intensity modulated arc therapy techniques, there is an increasing need for validation of treatment delivery in three‐dimensional (3D) space. A commercial dosimetry device ArcCHECK™ (Sun Nuclear Corporation, Melbourne, FL, USA) can be used in conjunction with 3DVH program. With this system, one can reconstruct the 3D dose distribution produced in the actual patient. In this work the authors evaluate the relative accuracy of the ArcCHECK™‐3DVH system using BANG3 (MGS Research, Guilford, CT, USA) polymer gel dosimeter. Methods: : About 15‐cm diameter and 20‐cm long cylindrical phantoms filled with BANG3 was used to simulate a patient, to which a volumetrically modulated arc therapy plan was created with Pinnacle 3 treatment planning software (Philips Healthcare, Andover, MA, USA). The plan (76 Gy total in 38 fractions) was designed for prostate radiotherapy using a 6 MV photon beam from an Elekta Synergy linear accelerator (Elekta AB, Stockholm, Sweden). The treatment was delivered to the simulated patient. The same plan was used to irradiate an ArcCHECK™ device with an insert plug. The point dose at the isocenter was measured using a Farmer‐type ionization chamber. The measured dose data were imported into the 3DVH program, which generated the 3D dose distributions projected onto the simulated patient. The dose data recorded in the polymer gel were read out using a MRI scanner and the 3D dose distribution delivered to the simulated patient was analyzed and compared with those from the 3DVH program and the Pinnacle 3 software. The comparison was accomplished by using the gamma index, overlaying the isodose lines for a set of data on selected planes, and computing dose‐volume histogram of structures. Results: : The dose at the center of the ArcCHECK™ device measured with an ionization chamber was 1.82% lower than the dose predicted by Pinnacle 3 . The 3D dose distribution generated by Pinnacle 3 was compared with those obtained by the ArcCHECK™‐3DVH system and BANG3. The gamma passing rates for criteria of 3% dose difference, 3 mm distance‐to‐agreement, and 25% lower dose threshold were 99.1% for the former and 95.7% for the latter. The mean and maximum PTV doses estimated by the 3DVH were 74.0 and 79.3 Gy in comparison to 74.4 and 76.5 Gy with Pinnacle 3 . Those values for BANG3 measurements were 74.7 and 79.5 Gy. The mean doses to rectum were 40.2, 39.8, and 38.8 Gy for Pinnacle 3, 3DVH, and BANG3, whereas the mean doses to the bladder were 26.7, 25.7, and 21.7 Gy, respectively. Conclusions: : The ArcCHECK™‐3DVH system provides an accurate estimation of 3D dose distribution in an actual patient within a clinically meaningful tolerance level. However, both 3DVH and BANG3 showed two noticeable differences from Pinnacle 3 . First, the measured dose throughout the PTV region was less uniform than Pinnacle 3 . Second, the dose gradient at the interface between PTV and rectum was steeper than Pinnacle 3 prediction. Further investigation may be able to identify the cause for these findings.